1993
DOI: 10.1200/jco.1993.11.12.2362
|View full text |Cite
|
Sign up to set email alerts
|

P-VABEC: a prospective study of a new weekly chemotherapy regimen for elderly aggressive non-Hodgkin's lymphoma.

Abstract: The P-VABEC regimen is active, well tolerated, and one of the briefest first-line chemotherapy regimens so far reported in the treatment of elderly patients with aggressive NHL. However, prospective randomized trials are needed to establish the real advantage of this regimen compared with other standard chemotherapy regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Initiatives to improve cytotoxic delivery without compromising benefit have led investigators to develop weekly, multiagent chemotherapy regimens. [20][21][22][23]25,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Improvements in supportive care enable the delivery of chemotherapy at standard doses and intensity to deliver maximum benefit to patients. 56 The minimum age of entry of 60 was chosen because patients younger than this were eligible for high-dose regimens and because this age carried prognostic significance in the international prognostic index (IPI) analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initiatives to improve cytotoxic delivery without compromising benefit have led investigators to develop weekly, multiagent chemotherapy regimens. [20][21][22][23]25,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Improvements in supportive care enable the delivery of chemotherapy at standard doses and intensity to deliver maximum benefit to patients. 56 The minimum age of entry of 60 was chosen because patients younger than this were eligible for high-dose regimens and because this age carried prognostic significance in the international prognostic index (IPI) analyses.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] During the 1980s, second-and third-generation combination chemotherapy regimens adapted for the elderly suggested similar outcomes with reduced toxicity in comparison to regimens for younger patients with similar histologies. [17][18][19][20][21][22][23][24][25] In the prednisolone, adriamycin, cyclophosphamide, etoposide, bleomycin, oncovin (vincristine), methotrexate (PACEBOM) alternating, weekly, combination chemotherapy regimen, the major toxicity problem was mucositis, which could be markedly reduced by the omission of methotrexate. 26 In this modified regimen, PAdriaCEBO, the greatest contributor to toxicity is adriamycin.…”
Section: Introductionmentioning
confidence: 99%
“…Grade III, IV toxicity was only reported for hematopoiesis (grade III and IV granulocytopenia and thrombocytopenia 12% each). Martelli et al [128] treated 60 chemonaive patients with the P-VAPEC protocol and reported a 75% CR rate, with no differences observed between patients treated for either 8 or 12 weeks. The 2-year overall survival was promising (64%), but currently awaits confirmation and comparison with, e.g.…”
Section: Pirarubicin (4)-o-tetrahydropyranyldoxorubicin Thpadriamycimentioning
confidence: 99%
“…There were four treatment-related deaths. Martelli et al (26) evaluated the combination of doxorubicin, etoposide, cyclophosphamide, vincristine, bleomycin and prednisone (P-VABEC) in 60 elderly patients. The CR rate was 75% and the projected survival a t 2 years was 64%.…”
Section: Discussionmentioning
confidence: 99%